2011
DOI: 10.1142/s0219455411004208
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study on in-Plane Behavior of Brick Masonry Wall Panels

Abstract: This paper presents the details of studies conducted on brick masonry units and wall panels. The investigation includes, compressive strength of brick unit, prisms, flexural strength evaluation, and testing of reinforced brick wall panels with and without opening. Nonlinear finite element analysis (FEA) of brick wall panels with and without opening has been carried out by simulating the actual test conditions. Constant vertical load is applied on the top of the wall panel and lateral load is applied in an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Ganapathi, et al [11] found that the compressive strength of brick prisms vary based on the failure pattern, Water absorption, mortar proportion and individual compressive strength of bricks. In this research, triplet brick prisms were cast using different cement mortar proportions 1:2, 1:3 and 1:4 with bond thickness of 10mm and cured for 15 days.…”
Section: B Determination Of Compressive Strength Of Triplet Brick Prismmentioning
confidence: 99%
“…Ganapathi, et al [11] found that the compressive strength of brick prisms vary based on the failure pattern, Water absorption, mortar proportion and individual compressive strength of bricks. In this research, triplet brick prisms were cast using different cement mortar proportions 1:2, 1:3 and 1:4 with bond thickness of 10mm and cured for 15 days.…”
Section: B Determination Of Compressive Strength Of Triplet Brick Prismmentioning
confidence: 99%
“…It is generally accepted that the presence of an opening in a masonry wall, due to functional or ventilation requirements, changes the response of the wall, and consequently affects the structure's behavior. The impact of openings on masonry walls and infills have been studied using numerous analytical simulations [2][3][4][5][6][7][8][9][10]. However, new sophisticated numerical models are required in order to overcome several fundamental issues such as the inherent complexity of non-linear masonry response subjected to both lowand high-level external load applications [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The in-plane behavior of unreinforced masonry (URM) in¯lled frames has been extensively reported, 1,[13][14][15] whereas few of studies on the behavior of in¯lled RC frames under the combined action of in-plane and out-of-plane loadings has been conducted, though it is a very common case for realistic building structures under seismic excitation. It is questionable that the analytical models that only consider inplane load action can be used to accurately predict the actual structural behavior of in¯lled frame buildings.…”
Section: Introductionmentioning
confidence: 99%